The atmospheric emissions in Spain: A regional analysis - Maria Luisa Chas Amil; Maria del Carmen Lorenzo Diaz; Xulia Guntin Araujo (European Regional Science Association (ERSA), 1998)
The gas emissions to the atmosphere are one the main and more actual environmental problems in the world. The effects of greenhouse gas emissions have been studied and treated recently in the Climate Change Conference in Kyoto. In the approved Kyoto Protocol, the European Union would reduce emissions by 8%, the United States by 7%, and Japan by 6%. The data for each country are used to implement policies and to make global decisions regarding the level of emissions allowed in the future. For this reason, a study more in depth about the origin and level of emissions from a regional perspective become necessary, due to the implications on the regional development. In this paper we will provide detailed information regarding atmospheric emissions in Spanish regions. Moreover, we will show that in many cases the atmospheric emissions are not directly related to the economic situation of each region. For this reason, environmental policies should pay attention to the regional differences within a country.
Keywords: 330